Maintaining Tradition to Establish Cohesion: An attempt of Sowing Local Wisdom-Based Multicultural Education in Lombok Community - Zaki, M (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2020)
Cultural heterogeneity and plurality of religions which grow, develop and survive in Lombok make this island such a pluralistic and multicultural miniature of Indonesia. This entity can be potentially integrative as a knit of social cohesiveness. However, in certain conditions and atmosphere, this diversity and culture can arise the emergence of conflict, violence and disaster if it is not managed properly. Muslims Sasak and Hindus Balineseethnic as the two largest communities in Lombok, often meet in space and stage conflict. The main factors are culture, economy, sectarianism, exclusivism, primordialism and multiculturalism education are still low.Despite repeated conflicts, it does not mean the social interaction of these two communities is not tolerated. Despite the conflicts that are always episodes, these two communities have local wisdom in the form of a religious festival of the perang topat tradition. This discourse is intended to describe the historical background of Islam and Hinduism in Lombok, analyze the causes of social conflict between the Muslim Sasak community and Hinduism Balinese ethnic in Lombok, as well as explore the local wisdom of the perang topat tradition as multicultural education base that can be made as a seeding of social cohesiveness.